Mean air flow rate in dysphonics - Sudhir Bhanu (Journal of All India Institute of Speech and Hearing, 1970)
Voice production involves a complex and precise control by the central nervous system of a series of events in the peripheral phonatory organs." The aerodynamicfactors play an important role in phonation. The measurement of air flow has gained importance in recent years in screening, assessing and treating voicedisorders.